Efek Analgesik Ekstrak Daun Pepaya (Carica papaya L.) dengan Menggunakan Metode Ransang Panas - Ria Ceriana; Riska Wahyuni; Nurhaliza Nurhaliza; Afniar Afniar; Khairul Muna; Siti Muria; Maghfira Misla; Aida Yunna; Silviyana Silviyana (Journal of Pharmaceutical and Health Research, 2022)
Medicinal plants have been known and used throughout the world for thousands of years. One type of plant that is often used as medicine is papaya leaf. The purpose of this study was to provide analgesic treatment with the hot stimulation method by taking samples of papaya leaf extract to be given to mice with a sonde method of oral administration. The design in this study used a completely randomized design (CRD) using 9 mice. Mice were divided into 3 groups, namely group 1 which was treated with 9 ml of papaya leaf extract, group 2 was mice that were given control treatment or only given distilled water and group 3 was mice that were injected with tramadol. All treatments were repeated 3 times. Data were analyzed descriptively and presented in tabular form. The results of the research on the anachetic effect that occurred by administering tramadol and papaya leaf extract were tested by heating mice showed that the treatment of jumping legs, licking feet, and not moving after 8 days of administration of tramadol drug liquid, papaya leaf extract and aquadest. Papaya leaves are proven to have analgesic effect by proving the treatment of mice that try to always lick their feet because they are exposed to hot stimuli.